Early pulmonary inflammation and lung damage in children with cystic fibrosis. Issue 4 (30th March 2015) - Schultz, André; Stick, Stephen
Abstract Individuals with cystic fibrosis (CF) suffer progressive airway inflammation, infection and lung damage. Airway inflammation and infection are present from early in life, often before children are symptomatic. CF gene mutations cause changes in the CF transmembrane regulator protein that result in an aberrant airway microenvironment including airway surface liquid (ASL) dehydration, reduced ASL acidity, altered airway mucin and a dysregulated inflammatory response. This review discusses how an altered microenvironment drives CF lung disease before overt airway infection, the response of the CF airway to early infection, and methods to prevent inflammation and early lung disease.